Monitoring of pond waters near Syowa Station (II) - Murayama, Haruta; Watanuki, Kunihiko; Nakaya, Shyu; Torii, Tetsuya (1984)
P(論文) The water samples collected in 1981 and 1982 were analyzed from the geochemical and environmental viewpoints. The water samples were collected from the following five lakes which have been selected as monitoring stations since 1978 : Mizukumi Stream (East Ongul Island), Lake O-ike (West Ongul Island), Lake Nurume (Langhovde), Lake Hunazoko (Skarvsnes) and Lake Skallen Oike (Skallen). Comparing the data obtained in this work with available previous data, the authors point out the results as follows. 1) Five lakes selected in 1978 were found suitable as monitoring stations. 2) Chemical compositions and dissolved salts in Lake Nurume and Lake Hunazoko have not changed markedly in the last fifteen years. 3) The amount of dissolved salts in three lakes, Mizukumi Stream, Lakes O-ike and Skallen Oike, has changed considerably. departmental bulletin paper